Expectations and Exits: The Effect of CEO Agency and Communion on Boards’ Expectancy Violations and Dismissal of CEOs Following Breaches of Stakeholder Rights - Zyung, J. Daniel (Organization Science, 2025)
How well CEOs manage and protect their stakeholders’ interests has risen as an important criterion in boards’ evaluation of CEOs. Research supports this notion by showing that CEOs who underinvest in corporate social responsibility (CSR) often face bleak job prospects. Therefore, when firms are involved in regulatory sanctions concerning stakeholders’ interests, CEOs may face the risk of dismissal, albeit to different degrees because boards may interpret such events in light of their expectations of CEOs’ stakeholder orientation. We suggest that these expectations are in part formed by boards’ perception of CEOs’ agency and communion—fundamental and distinct motives that signal CEOs’ differential commitment to personal competence, independence, control, and managing relationships with stakeholders. Building upon expectancy violations theory, we argue that following stakeholder-related regulatory sanctions, a CEO faces a higher likelihood of dismissal when perceived by the board as more communal or less agentic but a lower likelihood of dismissal when perceived as more agentic or less communal. We also posit that such tendencies hinge on firms’ CSR efforts and media sentiment, which further affect boards’ expectations of CEOs’ stakeholder management. A series of analyses shows strong support for our predictions, offering novel insights into the role of CEOs’ agency and communion in influencing CEOs’ career outcomes following stakeholder regulatory sanctions. Supplemental Material: The online appendix is available at https://doi.org/10.1287/orsc.2022.17114 .